The Effectiveness of Toddler Classes in Improving the Nutritional Quality of Infants Receiving MP-ASI at the Popayato Timur Community Health Center - Silfia Nahdyatus Shoima; Reny Retnaningsih (International Journal of Medicine and Health, 2025)
The quality of complementary feeding (MP-ASI) for infants aged 6–23 months is a key factor in supporting growth and preventing early nutritional problems. However, MP-ASI practices that do not comply with recommendations are still common, especially in areas with limited access to nutrition information and education. One of the promotive-preventive efforts developed in primary health care is the implementation of toddler classes. This study aims to analyze the effectiveness of toddler classes in improving the nutritional quality of infants receiving MP-ASI in the working area of the Popayato Timur Community Health Center. This study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 33 infants aged 6–23 months selected using a total sampling technique. Data were collected through infant anthropometric measurements to assess nutritional status based on indicators of weight for age (BW/A) and weight for length/height (BW/H), as well as assessing the quality of MP-ASI using quality scores before and after the intervention. Data analysis was carried out descriptively and inferentially using paired statistical tests. The results showed an increase in the quality of complementary feeding (MP-ASI) after the implementation of toddler classes, accompanied by improvements in infant nutritional status based on indicators of weight for age and weight for height, with a statistically significant difference between conditions before and after the intervention. In conclusion, toddler classes are effective in improving the quality of complementary feeding and infant nutritional status, thus potentially being an applicable educational strategy in efforts to improve infant nutrition in primary health care.